2000
DOI: 10.1108/09544780010320232
|View full text |Cite
|
Sign up to set email alerts
|

The propagation of quality management concepts in the Indian manufacturing industry: some empirical observations

Abstract: Presents findings from a study that investigated the propagation of quality management practices among Indian manufacturing companies over a period of 16 years from 1980 to 1996. Reports the findings of a mail questionnaire survey conducted on 500 selected companies from 14 manufacturing sectors. The extent to which quality management practices have been implemented is reported and the obstacles to adoption are identified. The spread of quality initiatives in various functional areas is analysed and discussed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Mechanisms, such as those ingrained within the alliance (e.g. customer-supplier focus and benchmarking, which are components of TQM) can allow effective learning to take place (Hill, 1996;Nesan & Holt, 1999;Mandal et al, 2000). Essentially, the organization, besides being a place where kinds of activities and operations are performed, becomes a 'giant laboratory' where people at all levels are constantly experimenting with and testing new practices and techniques.…”
Section: The Learning Organizationmentioning
confidence: 98%
“…Mechanisms, such as those ingrained within the alliance (e.g. customer-supplier focus and benchmarking, which are components of TQM) can allow effective learning to take place (Hill, 1996;Nesan & Holt, 1999;Mandal et al, 2000). Essentially, the organization, besides being a place where kinds of activities and operations are performed, becomes a 'giant laboratory' where people at all levels are constantly experimenting with and testing new practices and techniques.…”
Section: The Learning Organizationmentioning
confidence: 98%
“…Difficulties in creating a supportive culture is one of the most frequently mentioned obstacles to TQM implementation (Mandal et al, 2000;Tata and Prasad, 1998). TQM initiatives will not succeed unless rooted in a supportive organisational culture ( James, 1992).…”
Section: Difficulties In Changing Organisational Culturementioning
confidence: 99%
“…Factor wise analysis of product quality in Indian industries (Motwani et al , 1994), ascribe towards satisfactory performance. Mandal et al (2000), dilating on the status of quality management practices in India, expresses similar viewpoints. It is concluded that with the liberalization of the Indian economy, India has seen spurt in the application of quality concepts.…”
Section: Quality Changes In Industriesmentioning
confidence: 90%